129k views
5 votes
Find the distance between the points (2,3) (-3,-6)

User MikeGM
by
4.6k points

1 Answer

4 votes

Answer:

10.3

Explanation:

As we move from (-3,-6) to (2,3), x increases by 5 (this is the horizontal distance between (2,3) and (-3,-6) ) and y decreases by 9 (vertical distance).

We apply the Pythagorean Theorem here:

d^2 = x^2 + y^2, or

d^2 = (5)^2 + (-9)^2 = 25 + 81 = 106

Thus, the distance between (2,3) and (-3,-6) is d = sqrt(106), or approx.

10.3.

User AQuirky
by
5.4k points